Znaczenia niepełnosprawności intelektualnej w dyskursie internautów - WOYNAROWSKA, AGNIESZKA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Agnieszka Woynarowska, Znaczenia niepełnosprawności intelektualnej w dyskursie internautów [The meanings of intellectual disability within the internet discourse]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 259-287. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.15 In the following article, the author presents an analysis of meanings projected onto intellectual disabilities by the internet users by referring to the cultural model of disability, the theory of social constructivism, as well as, to the post-structuralist discourse theories. In accordance with the cultural model of disability theory, the author perceives intellectual disability as generated by social practices, and as a “product” of discourse. A discourse perceived as a “system of statements” and as a practice that shapes the subjects which it speaks of. From this perspective, intellectual disability is perceived as a phenomenon created by its continuing interpretations. By applying the critical discourse analysis, the article presents an answer to k users? The presented means of comprehending and perceiving intellectual disability, its revealed meanings included in the internet discourse dthe question: how is intellectual disability defined and interpreted within the internet discourse, what meanings are projected onto intellectual disability by the networetermine the current assortment of practices regarding how society responds to otherness.